Vulnerabilidad de los servicios ecosistémicos hidrológicos al cambio climático en Mesoamérica - Imbach, Pablo A.; Molina, Luis; Locatelli, Bruno; Corrales, Lenin (CATIE, Turrialba (Costa Rica), 2015)
1 ilustración, páginas 32-43